1983
DOI: 10.1038/bjc.1983.269
|View full text |Cite
|
Sign up to set email alerts
|

Sister chromatid exchange in lymphocytes from renal transplant recipients with and without cancer

Abstract: (range 9.1-19.9). This was significantly (P<0.01) higher than the mean value of control subjects. The mean SCE frequencies in 3 of these 7 patients fell within the control range and in 4 of these patients was above the control range. These results suggest that some immunosuppressed kidney transplant recipients are liable to chromosomal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Additionally, in renal transplant recipients, the amount of chromosomal injury in lymphocytes seems to be related to the occurrence of cancer [18]. However, no published data currently relates the occurrence of MN to distinct surgical procedures or the concomitant therapy typically used in solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in renal transplant recipients, the amount of chromosomal injury in lymphocytes seems to be related to the occurrence of cancer [18]. However, no published data currently relates the occurrence of MN to distinct surgical procedures or the concomitant therapy typically used in solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, azathioprine is considered safer than other drugs, such as mycophenolate or alkylating agents, and can be used to replace them in pregnant women with autoimmune disease or organ transplantation. Of some concern, however, older studies reported a rise of sister chromatid exchange frequency in patients treated with azathioprine [37,38]. Whether such a mild chromosome damage may have long-term consequences in the mothers and their newborns is unknown at present.…”
Section: Nucleotide Synthesis Inhibitorsmentioning
confidence: 99%